2010
DOI: 10.1007/s11705-010-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance of Co-Mo-Ce-K/γ-Al2O3 catalyst for the shift reaction of CO in coke oven gas

Abstract: The catalytic performance of Co-Mo-Ce-K/γ-Al 2 O 3 catalyst for the shift reaction of CO in coke oven gas is investigated using X-ray diffraction (XRD) and temperature-programmed reduction (TPR). The results indicate that Ce and K have a synergistic effect on promoting the catalytic activity, and the Co-Mo-Ce-K/γ-Al 2 O 3 catalyst with 3.0 wt-% CeO 2 and 6.0 wt-% K 2 O exhibits the highest activity. CeO 2 favors Co dispersion and mainly produces an electronic effect. TPR characterization results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the fresh catalyst, no crystalline MoO 3 or Co oxides have been detected, suggesting a very high dispersion of the active components. 12,40 The diffraction peaks of the fresh sample are due to the alumina support. When the catalyst is used for 1 year, the active components are still not detected, suggesting they are not aggregated during the industrial usage, but there is a very weak peaks shown at 29.01°, which is tentatively assigned to the [220] plane of Co 2 AlO 4 , where Co is in Co 2+ and Co 3+ form, as suggested by the blue color of the samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fresh catalyst, no crystalline MoO 3 or Co oxides have been detected, suggesting a very high dispersion of the active components. 12,40 The diffraction peaks of the fresh sample are due to the alumina support. When the catalyst is used for 1 year, the active components are still not detected, suggesting they are not aggregated during the industrial usage, but there is a very weak peaks shown at 29.01°, which is tentatively assigned to the [220] plane of Co 2 AlO 4 , where Co is in Co 2+ and Co 3+ form, as suggested by the blue color of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are other possible benefits of gasification, e.g., more stable solid waste residues; ability to safely destroy hazardous wastes; lower visual impact; and greater public acceptance. However, there have been always impurities left in the gasified products. Of these impurities, H 2 S tends to be present at the highest concentration in raw coal-derived syngas, but can vary significantly (1000–13 000 ppmv) depending on the sulfur level in the feed coal. This major impurity can have deleterious impacts on the downstream processing of syngas, and it is important to understand its effect on the performance of the conventional water–gas shift catalyst, which has been widely used in natural gas and oil conversion for decades. In this regard, the conventional water–gas shift catalyst based on Fe or Cu are easily deactivated by the H 2 S. , …”
Section: Introductionmentioning
confidence: 99%